2021
DOI: 10.3390/plants10020375
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Protocols for Arabidopsis Shoot and Root Protoplast Cultivation

Abstract: Procedures for the direct regeneration of entire plants from a shoot and root protoplasts of Arabidopsis thaliana have been optimized. The culture media for protoplast donor-plant cultivation and protoplast culture have been adjusted for optimal plant growth, plating efficiency, and promotion of shoot regeneration. Protocols have been established for the detection of all three steps in plant regeneration: (i) chromatin relaxation and activation of auxin biosynthesis, (ii) cell cycle progression, and (iii) conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…As shown in Figure 2 , we found that ~89% of the cells in the protoplast suspension are viable, as indicated by their round shape with strong fluorescent signals ( Supplemental Figure S4 ). This result was further substantiated by the time-lapse Rhodamine 123 staining [ 47 ] with most of the cells exhibit fluorescent signals in the corresponding time point ( Supplemental Figures S5 and S6 ).…”
Section: Resultsmentioning
confidence: 65%
“…As shown in Figure 2 , we found that ~89% of the cells in the protoplast suspension are viable, as indicated by their round shape with strong fluorescent signals ( Supplemental Figure S4 ). This result was further substantiated by the time-lapse Rhodamine 123 staining [ 47 ] with most of the cells exhibit fluorescent signals in the corresponding time point ( Supplemental Figures S5 and S6 ).…”
Section: Resultsmentioning
confidence: 65%
“…Previous studies have shown that cellular regeneration by callus formation from root explants initiates with divisions of pericycle cells, rather than dedifferentiation and cell cycle re-entry of root cells (17). To our knowledge, cell cycle re-entry of protoplasts derived from Arabidopsis roots has not yet been achieved (11,17). To understand whether bioprinted meristematic and differentiated root cells enter the cell cycle, we evaluated the bioprinted cells for divisions and microcallus formation.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the formed microcalli expressed the endodermal marker SCR. Previous studies showed that callus formation from roots explants was initiated by pericycle cells differentiating into cells resembling root meristems (11,17). However, the expression of SCR in the bioprinted microcalli indicates that in addition to pericycle-derived microcallus formation, another reprogramming mechanism might trigger microcallus formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported 2730 , we prepared protoplasts from the leaves and roots of an Arabidopsis CCA1::LUC transgenic plant. Protoplasts of leaves are mainly mesophyll cells 27 and those of roots are presumedly a heterogeneous population with different cell types 31,32 . Cells derived from the protoplasts of leaves and roots are hereafter referred to as leaf-derived cells and root-derived cells, respectively.…”
Section: Resultsmentioning
confidence: 99%